The role of brand commitment and external information in urban consumers’ organic produce choices: Evidence from Japan and China - Runan Yang; Hironori Yagi; Katsuhito Fuyuki (PLoS ONE, 2025)
Although organic agriculture brands are growing globally, urban consumer uptake in East Asia remains modest. We examine how brand commitment and external certification information shape willingness to pay (WTP) for organic vegetables based on multiple-store memory model. Online surveys of adult urban consumers in Japan (n = 412) and China (n = 422) are followed by a choice experiment in which respondents are randomly assigned to external certification information. Using latent profile analysis, we segment consumers’ brand commitment into five groups and estimate conditional logit models of choice and WTP. Results show that higher brand commitment and external certification information increase WTP for organic cabbage and tomatoes. Among Chinese consumers, information does not significantly affect WTP for carrots, indicating product-specific value perceptions. In Japan, information about semi-organic certification raises WTP for tomatoes, especially among high-brand commitment segments. The study contributes theoretically by linking brand commitment with information sensitivity to explain consumer heterogeneity, and by highlighting the importance of tailored marketing strategies. Our findings emphasize the need for targeted communication to enhance organic produce consumption in urban Asian markets.